2019
DOI: 10.1016/j.ejpb.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Targeted chemo-sonodynamic therapy treatment of breast tumours using ultrasound responsive microbubbles loaded with paclitaxel, doxorubicin and Rose Bengal

Abstract: Mastectomy is common surgical treatment used in the management of breast cancer but has associated physical and psychological consequences for the patient. Breast conservation surgery (BCS) is an alternative to mastectomy but is only possible when the tumour is of an appropriate size. Neo-adjuvant chemotherapy has been successfully used to downstage tumours and increase the number of patients eligible for BCS. However, the chemotherapies used in this approach are non-targeted and often result in significant si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 24 publications
2
41
0
1
Order By: Relevance
“…In numerous pilot studies, microbubbles have been identified as a mechanism for encapsulating drugs, such as DOX and paclitaxel, for drug delivery [14,15,16,17]. The carried drug within bubbles could be triggered release upon US sonication, achieving local drug delivery while decreasing the drug exposure in blood circulation [18,19,20,21,22]. Additionally, bubbles exhibit a bi-functional characteristic that merges ultrasonic diagnosis with therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In numerous pilot studies, microbubbles have been identified as a mechanism for encapsulating drugs, such as DOX and paclitaxel, for drug delivery [14,15,16,17]. The carried drug within bubbles could be triggered release upon US sonication, achieving local drug delivery while decreasing the drug exposure in blood circulation [18,19,20,21,22]. Additionally, bubbles exhibit a bi-functional characteristic that merges ultrasonic diagnosis with therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, they have an extra advantage of allowing imaging of the tumour by ultrasound techniques [49]. A successful trial for nanobubbles being used as carriers for doxorubicin as an anticancer drug on the basis of in vitro and in vivo studies was reported by Rapaport et al [50]. They used an ultrasound external source to cause disturbances for the aggregated nanobubbles that in turn started the doxorubicin release.…”
Section: Nanobubblesmentioning
confidence: 99%
“…US contrast agents are also well‐suited for a variety of therapeutic applications including drug‐delivery for anticancer therapy, atherosclerosis therapy, thrombolytic therapy, gene therapy and so on (Logan et al, ; McEwan et al, ; Zhou et al, ). Nevertheless, this review mainly summarizes the therapeutic applications of MBs in cancer‐related applications.…”
Section: Therapeutic Applications Of Microbubblesmentioning
confidence: 99%